Diamond: The Game – a board game for secondary school students promoting scientific careers and experiences. (30th June 2022) - Murray, Claire; Dunstan, Matthew; Heron, Catherine; Holland, Laura; Palmer, Sophy; Price, David; Basham, Mark
Abstract : page_1 other Diamond: The Game is a board game designed for secondary school students (aged 11–18) to enable them to explore a broad variety of science, technology, engineering and mathematics (STEM) careers, STEM subjects and life as a scientist. Board games are a reusable and entertaining way to directly engage students in STEM, but careful consideration of mechanics, messages and accessibility is required to successfully deliver on this goal. Diamond: The Game was designed and evaluated against these considerations. The inclusive approach to design resulted in a better and more accessible game for all. Its success is further evident in the rise in the number of players who would consider a career as a scientist or an engineer after playing. The opportunities to explore collaboration, failure and page_2 other the interdisciplinary nature of science in the game were particularly highlighted in discussions with students, teachers and careers advisers.